Real-time velocity profile generation of particle conveying using electrodynamic sensor - Mohd. Fua'ad Rahmat, 1966-; Mohd. Hezri Fazalul Rahman; Student Conference on Research and Development (2001 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2001)
40